Quantum-Enhanced Medical Imaging: Exploring the Role of Entangled Photons in Ultra-High-Resolution Diagnostic Techniques - Musa, Suhad Salam Hamid; Badawi, Zahraa Hassan Neima; Mohammed, Naala Fawzy khalaf; yaseen, Aisha yaseen Ahmed; Mohommed, Amna Mohammed Abdul Latif (American Journal of Biomedicine and Pharmacy, 2025)
In modern medical facilities, the effectiveness and rapidity of diagnosis are absolutely crucial for shaping and determining proper treatment policies. Due to the fundamental limitations that are inherent in traditional X-ray computed tomography devices, there is a highly critical requirement for a new ultra-high-resolution diagnostic imaging method that can improve patient outcomes. Quantum theory provides interesting insights, indicating that a pair of photons can propagate in distinct directions while still being able to maintain an identical phase relationship. Specifically, when such photons are tightly focused on the body, the positions of these photons become localized; however, their wavenumber vectors continue to remain entangled. Under these specific conditions, the wavelength of the entangled photons can be precisely measured in the far field, all while ensuring that the tight localization remains intact within the body. The size of the focal point involved is subsequently determined by these wavenumber vectors of the entangled photons, which ensures that image quality is maintained. This is significant even in cases where the wavelength of the entangled photons in the far field exceeds that of the individual photons. Moreover, because the device can be fabricated using a straightforward and simple scheme, it allows for the exploitation of quantum properties, making it an innovative approach for the development of ultra-high-resolution diagnostic apparatus that can potentially revolutionize diagnostic imaging in healthcare.